Análisis, diseño y generación de información gerencial para la toma de decicisiones de una clínica de especialidades médicas - Suárez Jaya, José Luis (2016)
The present project is to analyze and design a strategic solution for generating information for management decision making in a clinical medical specialty. This document there are four chapters: The first chapter describes the current situation of the organization, also it contains all the scientific and theoretical support used in the development of this project. The second chapter provides a description of analyzing and designing of DATA WEREHOUSE that contains an operational data store as the source of information. The proposed methodology is Ralph Kimball because it provides design approach (the bottom-up design): Where the data marts facilitating reports and analysis are created first; these are then combined together to create a broad data warehouse. The third Chapter describes the construction of ODS and DWH, with their respective operational tests and the use of a self-service tool for designing a dashboard and display of relevant information. Also it chapter describes the conclusions and recommendations about developing of DATA WAREHOUSE